Manifestations of Technical Giftedness in Senior High School Students - Panfilov, Aleksey (International Journal of Psychosocial Rehabilitation, 2020)
Background: The socio-economic realia of Russian development require efficient professional selection and consideration of a person's individual psychological traits during training that provide for successful human– technology interaction. This makes topical studying a special ability – technical giftedness and its manifestations during school education. The paper describes the concept of "giftedness", reveals the structural components of technical giftedness, and gives the analysis of Russian and foreign research findings on developing a person's technical giftedness.Methods: For identifying gifted senior high school students, an integrated approach was used which includes a wide variety of methods: observation in various situations; psycho-diagnostic trainings and studies using psychometric diagnostics.Results: The signs of technical giftedness were identified as follows: instrumental signs – mechanical comprehension, spatial imagination, analytical and synthetic skills, intellectual lability; motivational signs – interest in technology, inclination to technical activities, inventing, design, individual professional preferences.Conclusions: During the empirical study, the experimental and control samples were divided by gender. Analyzing the empirical study findings leads to the following conclusion: the motivational component of technical giftedness in senior high school students has to be actualized; technical giftedness is directly related to the development of spatial imagination and synthetic skills. Socio-pedagogical stereotypes associated with boys having better technical thinking than girls and boys with high technical giftedness scores being oriented to engineering professions have to be overcome.